Decisions about risk taking: Elaborate dynamics between guests and hosts of peer-to-peer accommodation during COVID-19 - Anan Hu; Jinyuan Pang; Xuena Gan (PLoS ONE, 2026)
This study explores the influence of COVID-19 on peer-to-peer accommodation, from perspectives of both market performance and guests’ mindset. Combination of qualitative and quantitative data, as well as analysis by smaller time unit, enables more subtle insights into participants’ behavior. Based on Event System Theory, authentic market data is examined to demonstrate the trend of demand and supply of Airbnb housing in New York City. Online reviews are investigated, using Structural Topic Model, to reveal how guests’ focuses transformed. Results show that peer-to-peer accommodation was stricken heavily by COVID-19 and subsequent events, where booking volume shrank more severely, and reacted faster to exogenous environment, compared to housing supply. Guests shifted their attention after COVID-19 happened, caring more about hygiene and social distance. The synchronization of fluctuation among multiple variables validates the assumption that exogenous events successively influenced guests’ attitude and market performance. Apropos of events, stronger incidents exhibited larger influence on market performance, and event timing affected exogenous events’ influence upon the industry. This research enriches Event System Theory and adds to the insights into elaborate dynamics among participants of peer-to-peer accommodation industry during COVID-19. The findings provide hospitality practitioners and governments with reference for future risk management.